Individual determinants of job satisfaction among young adults in Poland - Śliwicki Dominik; Szczepaniak Małgorzata; Szulc-Obłoza Agnieszka (International Journal of Management and Economics, 2025)
Job satisfaction is an essential factor influencing employees as well as employers. This study aims to identify and compare overall job satisfaction determinants among young adults in Poland in two dimensions, i.e., economic and socio-demographic. The ordered logit model was built upon the data collected in 2021 in a survey using the Computer Assisted Web Interview technique on a sample of 304 young adults aged 18–29 years in Poland. The results indicate that young adults’ job satisfaction in Poland is determined by wage satisfaction to the highest extent. It was also demonstrated that the impact of economic factors on job satisfaction is much stronger than that of socio-demographic ones. Individual income increases the probability of high job satisfaction to a greater extent than disposable income per person in a household. Moreover, the economic profile of education increases the probability of greater job satisfaction.